Implementasi Model Belajar Kolaboratif Kelas Digital di Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Mohammad Badru Tamam (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Collaboration has become a 21st century trend. The community's need to think and work together on issues of significant concern has increased, shifting the emphasis from individual efforts to group work, from independence to society. This review tries to provide a clear concept of collaborative learning, keeping in mind the main elements in a collaborative setting and looks at the benefits of following cooperative learning. Collaboration is a philosophy of interaction and personal lifestyle in which individuals are responsible for their actions, including learning and respecting the abilities and contributions of their peers. The concept of CL, grouping and pairs of students to achieve learning goals, has been widely researched and recommended; the term CL refers to teaching methods in which students at various levels work together in small groups to achieve common goals. The students are responsible for each other who learns and themselves. Thus, the success of one student helps other students become successful. Rapid technological developments have changed the way of learning in learning classrooms. At present teachers have used technology to help them face the challenges posed by existing changes and developments. The development of digital collaborative learning opens up careful planning and mature feasibility studies so that its application and development are able to answer various problems in learning, education, the world of work, and science. With the implementation of the collaborative learning model the digital class has the advantage of improving thinking skills, communication, collaboration and the use of digital-based technology as a learning tool.